Planet Earth is screaming. Will you listen? - Palla, M.; Bethani, H.; Mourtou, L.; Argyri, P. (Open Schools Journal for Open Science, 2020)
The problem we are trying to solve is associated with air pollution caused by the use of unsustainable energy sources, especially by cars. Our aim is to inform people about the problem of air pollution and motivate them. As a solution, we are presenting the use of sustainable energy sources. The main goal of our project is to create the environmentally ideal city (based on the city we live in, New Smyrna), in which only sustainable energy sources will be used. Firstly, our project aims to make people understand the problem by presenting the consequences of the use of unsustainable energy sources through videos, researches, statistics and even games, to promote sustainable energy sources and make the advantages of them known to the people and to create a city that runs completely on sustainable energy sources, as well as the presentation of the city in a model.